Kesejahteraan Subjektif pada Emerging Adulthood Ditinjau dari Self Compassion dan Religiusitas pada Remaja Akhir - Nugraha, Aditya Dedy (Psyche 165 Journal, 2023)
Mental health during adolescence is crucial, as untreated issues can lead to problems in early adulthood. Early adulthood, the age period from late teens to late 20s, comes with various developmental tasks: selecting life partners, fulfilling social roles, achieving emotional independence, and establishing a household. Improving individual well-being is one way to address mental health and enhance subjective well-being, which includes life satisfaction, positive emotions, and reducing negative emotions. Self-compassion and religiosity are factors influencing subjective well-being during emerging adulthood. The research used a quantitative correlational method with self-compassion and religiosity as independent variables, and subjective well-being as the dependent variable. The findings indicate that self-compassion and religiosity together contribute 32,7% to subjective well-being in emerging adulthood. Self-compassion plays a larger role (32,2%) compared to religiosity (0,5%). These results of these research, highlight the importance of self-compassion and religiosity in improving individual subjective well-being. Enhancing these factors can help individuals face challenges, improve emotional resilience, and adopt healthier lifestyles, resulting in positive benefits for subjective well-being during emerging adulthood. Giving attention to adolescent mental health and developing self-compassion and religiosity during emerging adulthood are crucial to enhancing individual subjective well-being and overall well-being in Indonesian society. Relevant authorities should implement policies to improve the quality of mental health in Indonesian communities, ensuring the well-being and growth of future generations.